Analisis Kritis Dogma Pneumatologis Dalam Liturgi Gereja Kristen Protestan Indonesia (GKPI) - Siregar, Martuani Sterne; Saragih, Denni Boy (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
In the modern era, the Lutheran tradition has recognized the need to enrich its theology to remain relevant to contemporary developments, one of which is through the exploration of pneumatological thought. As part of this tradition, GKPI also faces similar challenges. The enrichment of pneumatological theology in GKPI can be pursued by enhancing the comprehensiveness of its dogma or improving the effectiveness of its communication to the congregation. This study aims to understand the position of GKPI’s pneumatological thought in relation to these two aspects. Using a qualitative method, the study found that GKPI possesses a comprehensive pneumatological dogma. However, a gap exists between the dogma and the liturgy in use, indicating an ineffective communication pattern. This gap constitutes a crucial point for the enrichment of GKPI’s pneumatological theology.